1995
DOI: 10.1007/bf02353639
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective binding properties of naproxen glucuronide diastereomers to proteins

Abstract: The stability of naproxen glucuronide (NAP-G) diastereomers was investigated in buffer, 0.3% and 3% human serum albumin (HSA) solutions, and human plasma. R-NAP-G was found to be less stable in phosphate buffer than its S-diastereomer, whereas incubation media containing protein in general increased the degradation rate of NAP-G but also caused a change of the stereoselective stability where the R-NAP-G was more stable than S-NAP-G. Reversible binding of NAP-Gs to HSA (0.3%) was investigated and compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…First, a significant amount of diclofenac AG may be oxidized to 4Ј-hydroxy diclofenac AG via the so-called "metabolite firstpass effect" before its egress from the hepatocytes into the bloodstream (Pang and Gillette, 1979). Second, acyl glucuronides, in general, exhibit a significantly reduced degree of plasma protein binding relative to the parent drug because of their greater hydrophilicity (Ojingwa et al, 1994;Bischer et al, 1995). Third, it is possible that because of rapid metabolism of diclofenac via this pathway, high local concentrations of diclofenac AG are achieved in the liver, which may saturate any binding to blood components.…”
Section: Discussionmentioning
confidence: 99%
“…First, a significant amount of diclofenac AG may be oxidized to 4Ј-hydroxy diclofenac AG via the so-called "metabolite firstpass effect" before its egress from the hepatocytes into the bloodstream (Pang and Gillette, 1979). Second, acyl glucuronides, in general, exhibit a significantly reduced degree of plasma protein binding relative to the parent drug because of their greater hydrophilicity (Ojingwa et al, 1994;Bischer et al, 1995). Third, it is possible that because of rapid metabolism of diclofenac via this pathway, high local concentrations of diclofenac AG are achieved in the liver, which may saturate any binding to blood components.…”
Section: Discussionmentioning
confidence: 99%
“…81) Among the drugs that become glucuronidated and interact covalently with HSA are furosemide, 77) salicylic acid, 82) gemfibrozil, 83) clofibric acid, 84) fenofibric acid, 84) and NSAIDs like tolmetin, 77,85) benoxaprofen, 80) zomepirac, 77) beclobric acid, 77) ibuprofen, 86) ibufenac, 86) suprofen, 81) ketoprofen, 87) and diflunisal. 88) Stereoselectivity was observed for, e.g., carprofen, 77) fenoprofen, 77) and naproxen 89) ; in all cases the R-forms exhibited the highest covalent binding. Photoactivated naproxen and frusemide, as well as photoactivated frusemide glucuronide, also bind covalently to HSA.…”
Section: Covalent Binding Of Drug Metabolitesmentioning
confidence: 91%
“…Moreover, our previous studies suggested that the ratio of reversible binding to human serum albumin (HSA) of NSAIDs-Glu, such as naproxen glucuronide and fenoprofen glucuronide, tends to be weaker than that of their parent NSAIDs. 37,38) Assuming that diclofenac glucuronide has a similar tendency, it is unsurprising that inhibition of OAT3-mediated MTX uptake by diclof- -and S-naproxen (g, h) at various concentrations at 37°C. Results are the mean of duplicate experiments.…”
mentioning
confidence: 99%